You're hired business basics every babysitter needs to know - Rissman, Rebecca (North Mankato, Minnesota Capstone Press, 2015)
Presents advice to babysitters on getting jobs, keeping a business going, and safe handling of babies and children
A gift from book Africa
Education
1 2 11 13
Keywords: Babysitters -- Juvenile literature; Babysitters